(untitled) (Global Journal of Human-Social Science, 2013)
Viewing litigation as an effective weapon in minority group politics, gay and lesbian rights activists in Canada and the United States turned to the judicial arena, seeking the courts’ affirmation of their fundamental right to marry. In contrast, Belgian and Spanish activists refrained from constitutional litigation, choosing instead to pursue marriage equality by appealing to national legislative and executive institutions, and developing insider strategies within the political parties. This paper explores the asymmetry between the four countries: it highlights the key differences and similarities among them and offers preliminary explanations for the disparities in strategies for marriage equality. It concludes that the strategies developed by same-sex marriage advocates in these four cases reflected their countries’ legal and political environment as well as their historical approach to social reform.